Management of deep-water sharks' by-catch in the Portuguese anglerfish fishery: from EU regulations to practice. (April 2018) - Moura, Teresa; Fernandes, António; Figueiredo, Ivone; Alpoim, Ricardo; Azevedo, Manuela
Abstract: The European Union banned fishing operations with trammel, entangling and gillnets in Portuguese continental waters at depths >200 m in consideration of the potential impact of fisheries on deep-sea sharks. Derogation could be considered if Member States demonstrate that by-catch mortality does not adversely affect this group of species. This regulation has had an impact on the trammel net fishery for anglerfish ( Lophius piscatorius and Lophius budegassa ), one of the most important Portuguese multi-species fisheries. This study evaluates the impact of this fishery on deep-water shark populations by looking at onboard observations of by-catch in the commercial fishery and by analysing survey catch composition. Results suggest that this fishery has a very low impact on deep-water shark populations: by-catch was <5% by weight of the total catch in 98% of the hauls conducted in the depth range allowed for this fishery (<600 m). Frequency of occurrence of deep-water sharks was also low. Etmopterus spinax and Etmopterus pusillus were the only species found to overlap with this fishery to any great extent; all the others largely distribute at depths greater than 600 m. A higher overlap is expected in hauls catching L. piscatorius, which seems to distribute at greater depths, but more information is needed to clarify the distribution pattern of this species. Scientific data supports the proposed change to the EU regulation. If necessary, future management measures may rely on spatial closures, but would require enhanced knowledge on species' spatial distributions and also on social and economic aspects of this fishery. Highlights: Conservation concerns for deep-water sharks led to the establishment of restrictive regulations. The ban on trammel net fisheries at depths >200 m had a negative impact on the anglerfish fishery. Results showed that deep-water sharks have low levels of occurrence in this fishery. Most deep-water shark species have a low spatial overlap with this fishery. New information provides scientific support to change an EU fisheries policy.